Analysis of a tapered rectangular waveguide for V to W millimeter wavebands - Lee, Sangsu; Son, Dongchan; Kwon, Jae Yong; Park, Yong Bae (Journal of Electromagnetic Engineering and Science, 2018)
An electromagnetic boundary-value problem of a tapered rectangular waveguide is rigorously solved based on eigenfunction expansion and the mode-matching method. Scattering parameters of the tapered rectangular waveguide are represented in a series form and calculated in terms of different rectangular waveguide combinations. Computation is performed to analyze reflection and transmission characteristics. Conductor loss by surface current density is also calculated and discussed.
Keywords: Conductor loss; Mode-matching method; Tapered rectangular waveguide